NoxO1 Controls Proliferation of Colon Epithelial Cells - Moll, Franziska; Walter, Maria; Rezende, Flávia; Helfinger, Valeska; Vasconez, Estefania; De Oliveira, Tiago; Greten, Florian R.; Olesch, Catherine; Weigert, Andreas; Radeke, Heinfried H.; Schröder, Katrin (Frontiers in Immunology, 2018)
Aim: Reactive oxygen species (ROS) produced by enzymes of the NADPH oxidase family serve as second messengers for cellular signaling. Processes such as differentiation and proliferation are regulated by NADPH oxidases. In the intestine due to the exceedingly fast and constant renewal of the epithelium both processes have to be highly controlled and balanced. Nox1 is the major NADPH oxidase expressed in the gut and its function is regulated by cytosolic subunits such as NoxO1. We hypothesize that the NoxO1-controlled activity of Nox1 contributes to a proper epithelial homeostasis and renewal in the gut. Results: NoxO1 is highly expressed in the colon. Knockout of NoxO1 reduces the production of superoxide in colon crypts and is not subsidized by an elevated expression of its homologue p47phox. Knock out of NoxO1 increases the proliferative capacity and prevents apoptosis of colon epithelial cells. In mouse models of DSS-induced colitis and AOM/DSS induced colon cancer, NoxO1 has a protective role and may influence the population of natural killer cells. Conclusion: NoxO1 affects colon epithelium homeostasis and prevents inflammation.